2013
DOI: 10.3892/br.2013.181
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of associations between MDM2 SNP309 polymorphism and gastric cancer risk

Abstract: Abstract. Epidemiological studies have been conducted to evaluate genetic variations of murine double minute 2 (MDM2) SNP309 associated with the risk of gastric cancer (GC), although evidence remains conflicting. To gain a better understanding of this relationship, a meta-analysis was performed. Several electronic databases were searched up to February 2013, in order to identify relevant case-control studies. Seven published case-control studies with 2,199 cases and 3,201 controls were included. In the overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…The G allele was revealed to act as a key factor for increasing the risk of GC, which is consistent with the study by Pan et al (29). In addition, in a meta-analysis, Chen et al (30) proposed that the G allele of the MDM2 T309G polymorphism is a high risk factor for developing GC. In the present study, a statistically significant difference was identified in the GG genotype distribution between GC patients and control subjects in the investigated Turkish population (OR=4.58; 95% CI, 1.18-17.79; P=0.022; Table III).…”
Section: Discussionsupporting
confidence: 78%
“…The G allele was revealed to act as a key factor for increasing the risk of GC, which is consistent with the study by Pan et al (29). In addition, in a meta-analysis, Chen et al (30) proposed that the G allele of the MDM2 T309G polymorphism is a high risk factor for developing GC. In the present study, a statistically significant difference was identified in the GG genotype distribution between GC patients and control subjects in the investigated Turkish population (OR=4.58; 95% CI, 1.18-17.79; P=0.022; Table III).…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, another MDM2 polymorphism (I/D) has been described in the promoter, which may affect the MDM2 expression (Bond et al, 2004;Hu et al, 2006) Considering the role of MDM2 in tumorigenesis, numerous investigations have been made on the effects of MDM2 polymorphisms on various diseases including cancers and several meta-analyses are published with conflicting results (Chen, Wu, & Ren, 2014;Duan & Li, 2017…”
Section: Discussionmentioning
confidence: 99%
“…In the meta‐analysis studies conducted by Chen et al (); Duan & Li. (); Zhuo et al () the MDM2 309T>G polymorphism was considered as a susceptibility factor for hepatocellular carcinoma as well as gastric and cervical cancers, respectively (Chen et al, ; Duan & Li, ; Zhuo, Ren, Li, Wu, & Zhou, ). In the meta‐analysis carried out by Xue et al, the MDM2 309T>G polymorphism was regarded as a susceptible factor for endometrial cancer, especially in Caucasians (Xue, Zhu, & Teng, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TP53 induces intracellular expression of MDM2, whereas the latter induces the downregulation of TP53, the auto‐regulatory feedback loop between TP53 and MDM2. The relationship between MDM2 SNP309 and GC risk was meaningful, especially in CGA for the H pylori ‐positive population group . Genotype analyses demonstrated that increased risk for development of CGA was correlated with the MDM2 309G and the P53 72Pro allele compared to the P53 72Arg allele and the MDM2 309T in an allele dose‐dependent manner …”
Section: Genetic Risk Factorsmentioning
confidence: 91%